Anti-Oxidant, Anti-Inflammatory and Anti-Angiogenic Properties of Resveratrol in Ocular Diseases - Allan Lançon; Raffaele Frazzi; Norbert Latruffe (Molecules, 2016)
Resveratrol (3,4′,5 trihydroxy-trans-stilbene) is one of the best known phytophenols with pleiotropic properties. It is a phytoalexin produced by vine and it leads to the stimulation of natural plant defenses but also exhibits many beneficial effects in animals and humans by acting on a wide range of organs and tissues. These include the prevention of cardiovascular diseases, anti-cancer potential, neuroprotective effects, homeostasia maintenance, aging delay and a decrease in inflammation. Age-related macular degeneration (AMD) is one of the main causes of deterioration of vision in adults in developed countries This review deals with resveratrol and ophthalmology by focusing on the antioxidant, anti-inflammatory, and anti-angiogenic effects of this molecule. The literature reports that resveratrol is able to act on various cell types of the eye by increasing the level of natural antioxidant enzymatic and molecular defenses. Resveratrol anti-inflammatory effects are due to its capacity to limit the expression of pro-inflammatory factors, such as interleukins and prostaglandins, and also to decrease the chemo-attraction and recruitment of immune cells to the inflammatory site. In addition to this, resveratrol was shown to possess anti-VEGF effects and to inhibit the proliferation and migration of vascular endothelial cells. Resveratrol has the potential to be used in a range of human ocular diseases and conditions, based on animal models and in vitro experiments.